Ceršaški govor - Koletnik, Mihaela (Jezik in slovstvo, 1999)
The dialect of the Western Slovenske gorice, where the speech of Ceršak belongs, is part of the Panonnic dialect group. It is characterised by the loss of tonemic oppositions and a later lenghtening of old reduced and short newly-acutised vowels, with the resulting present-day distinction between reflections for these acutised and permanetly long vowels. In declension and conjugation, the unshifting stress on the base syllable prevails. Complex and compound syntactic patters do not differ significantly from those of the standard literary language.
Keywords: Slovene; slovenščina; dialectology; dialektologija; narečja; dialect; Slovenske gorice; Ceršak